ANALISIS YURIDIS PELANGGARAN KODE ETIK PROFESI POLRI OLEH PERSONEL SATUAN BRIMOB POLDA SUMATERA UTARA YANG MELAKUKAN KASUS TINDAK PIDANA - Muhammad Ridwan Lubis, Muktar Lutfi, (NERACA KEADILAN, 2025)
The implementation of the duties of Polri personnel, especially members of the North Sumatra Police Mobile Brigade Unit, is very vulnerable to violations of the professional code of ethics and criminal acts that can damage the image of the Police institution. These violations often occur in handling criminal cases, in the form of abuse of authority, excessive use of violence, and violations of applicable legal procedures. This condition creates public distrust of the Polri and hinders the realization of fair and professional law enforcement. Based on this background, this study formulates three main problems, namely: first, the form of violation of the professional code of ethics committed by personnel of the North Sumatra Police Mobile Brigade Unit who commit criminal cases; second, the mechanism for monitoring and enforcing the police professional code of ethics against personnel of the North Sumatra Police Mobile Brigade Unit who commit criminal cases; and third, legal accountability for personnel of the North Sumatra Police Mobile Brigade Unit who are proven to have violated the professional code of ethics. This study uses a normative juridical method by examining laws and legal literature related to the Polri professional code of ethics, internal supervision mechanisms, and aspects of legal accountability of Polri personnel. The results of the study indicate that violations of the code of ethics of the North Sumatra Police Mobile Brigade Unit personnel generally take the form of abuse of authority, disproportionate use of violence, and neglect of legal procedures. The mechanism for monitoring and enforcing the code of ethics is carried out through internal institutions such as Propam and the Police Code of Ethics Commission, as well as external supervision by Kompolnas and the community. Legal accountability includes ethical, disciplinary, and criminal areas that complement each other to maintain accountability and professionalism. This study recommends strengthening internal and external supervision and strict law enforcement against violations of the code of ethics to increase public trust in the Police and ensure fair law enforcement.